Vision vessel smart bottle / Maizatul Maisarah Mustapha … [et al.] - Mustapha, Maizatul Maisarah; Hasbullah, Nur Farhanah Athira; Zahar, Nurul Farah Nabilah; Wan Azmi, Wan Nuralia Batrisyia; Kamis, Rohaiza (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Millions of individual worldwide suffer from vision impairment, making even basic tasks like as staying hydrated difficult. This paper highlights the VisionVessel Smart Bottle, a revolutionary technology created to meet the specific needs of the blind and visually impaired people. The VisionVessel has features such as digital braille for water temperature indicator, auditory reminders for hydration, and a UV self-cleaning mechanism, which promote user independence and general well-being. Hence, this new of invention bridges a gap in the current smart water bottle industry, which is mostly geared toward fitness enthusiasts. Furthermore, VisionVessel provides a practical solution by including vital features for the visually impaired, such as a removable supplement compartment with audible reminders and a self-cleaning function that uses UV light. Braille indications are automatically updated based on water temperature, ensuring safe and informed consumption. Hence, VisionVessel Smart Bottle has the potential to be a commercially successful device that empowers users and improves their quality of life. Nevertheless, this invention makes an important contribution to the assistive technology landscape by enhancing accessibility and independence for the visually impaired. The proposed idea is in the prototype development stage, with additional study required for optimization and large-scale production